Twenty Novel Disease Group-Specific and 12 New Shared Macrophage Pathways in Eight Groups of 34 Diseases Including 24 Inflammatory Organ Diseases and 10 Types of Tumors - Lai, Bin; Wang, Jiwei; Fagenson, Alexander; Sun, Yu; Saredy, Jason; Lu, Yifan; Nanayakkara, Gayani; Yang, William Y.; Yu, Daohai; Shao, Ying; Drummer, Charles; Johnson, Candice; et al. (Frontiers in Immunology, 2019)
The mechanisms underlying pathophysiological regulation of tissue macrophage (Mφ) subsets remain poorly understood. From the expression of 207 Mφ genes comprising of: 31 markers for 10 subsets, 45 transcription factors (TFs), 56 immunometabolism enzymes, 23 trained immunity (innate immune memory) enzymes, and 52 other genes in microarray data; we made the following findings: 1) When grouping 34 inflammation diseases and tumor types into eight categories there was differential expression of the 31 Mφ markers and 45 Mφ TFs; highlighted by 12 shared and 20 group-specific disease pathways; 2) The expression of M1 Mφ markers is higher in Mφ in lung, liver, spleen, and intestine compared to lean adipose tissue Mφ physiologically; 3) Pro-adipogenic TFs C/EBPα, PPARγ, and proinflammatory adipokine leptin upregulate the expression of M1 Mφ markers; 4) among ten immune checkpoint receptors (ICRs), LLSI-Mφ, and bone marrow (BM) Mφ express higher levels of CD274 (PDL-1) than that of ATMφ presumably to counteract the M1 dominant status via its reverse signaling of CD274; 5) among 24 intercellular communication exosome mediators, LLSI- and BM- Mφ prefer to use RAB27A, STX3 than RAB31 and YKT6, suggesting new inflammatory exosome mediators for propagating inflammation; 6) Mφ in peritoneal, and LLSI-Mφ upregulate higher levels of immunometabolism enzymes than ATMφ; and 7) Mφ from peritoneum, and LLSI-Mφ upregulate more trained immunity enzyme genes than that of ATMφ. Our results suggest that multiple new mechanisms including cell surface, intracellular immunometabolism, trained immunity and TFs may be responsible for disease group-specific, and shared pathways. Our findings have provided novel insights on pathophysiological regulation of tissue Mφ, disease group-specific and shared pathways of Mφ, and novel therapeutic targets for cancers and inflammations. (total words: 271)